THE EFFECTIVENESS OF DBH-CHT (Tobacco Excise Revenue Sharing Fund) ASSISTANCE FOR TOBACCO FARMER GROUPS IN PASIGARAN VILLAGE, SUMEDANG REGENCY - Anuar Januar Rahman; Ivonne Ayesha (Ikatan Dosen Menulis, 2026)
This study aims to analyze the effectiveness of the Tobacco Products Excise Revenue-Sharing Fund (DBHCHT) assistance for tobacco farmer groups in Pasigaran Village, Sumedang Regency. The research employed a quantitative descriptive method by distributing questionnaires to 30 respondents who are members of the farmer groups. The results indicate that overall, the DBHCHT assistance program is categorized as highly effective, achieving a score of 77.1%. The indicators with the highest scores were the alignment of the assistance with farmers’ needs (85.5%) and the quality and availability of inputs (80.0%), both of which fall into the highly effective category. Meanwhile, the implementation process (70.0%) and utilization transparency (73.3%) were categorized as effective, suggesting challenges related to program governance. Thus, it can be concluded that the DBHCHT program has provided tangible benefits for tobacco farmers in Pasigaran Village, although improvements in implementation coordination and transparency are needed to enhance its optimal, equitable, and sustainable impact.